The Implementation of Law Enforcement In Combating Terrorist Financing in Indonesia - Pati, Nova Vincentia; Senewe, Emma Valentina; Kalalo, Merry Elisabeth; Waha, Caecilia Johanna; Lumunon, Theodorus HW (Indonesian Journal of International Law, 2024)
Law enforcement in Indonesia terrorism has encountered enormous difficulties when it comes to combating terrorist financing. In contrast, the terrorists who have been imprisoned found that the punishment given by the judge in the court and the deradicalization programs offered by BNPT, the National Counter Terrorism Agency, does not deter them from recidivism. Our research question is whether or not the implementation of law enforcement in combating terrorist financing in Indonesia has deterred terrorists from re-offending. The methodology used in this research is a qualitative method that employs two case studies through in-depth interviews to determine whether or not the implementation of law enforcement in combating terrorist financing through penal and non-penal laws in Indonesia has made ex-convict terrorists refrain from rejoining terrorist organizations. The findings show a gap in the law that needs to be corrected to make the implementation of law enforcement in combating terrorist financing work properly. The spirit of progressive law, namely to offer justice and to provide happiness to the people and aligned with the aims of forming the Indonesian government, was stated in the Preamble of the 1945 Constitution of the Republic of Indonesia, Pancasila, and the body of the 1945 Constitution of the Republic of Indonesia. It concerned human rights principles, and a former convict of terrorist funding is a victim of economic, social, cultural, psychological, and political injustice. The main reason for former convicts of terrorist funding joining terrorist funding groups is because they experienced mistreatment by their families, their communities, and even their government, who in this case is the Indonesian government.